Optimization of the coating of octyl-CALB with ionic polymers to improve stability and decrease enzyme leakage. Issue 1 (2nd January 2018) - Fernandez-Lopez, Laura; Virgen-OrtÍz, Jose J.; Pedrero, Sara G.; Lopez-Carrobles, Nerea; Gorines, Beatriz C.; Otero, Cristina; Fernandez-Lafuente, Roberto
Abstract: Lipase B from Candida antarctica (CALB) immobilized on octyl-agarose (OC) was submitted to coating with polyethylenimine (PEI) and dextran sulfate (DS). Using lowly loaded enzyme preparations, the properties of OC-CALB preparations hardly improved, suggesting too large the distance between enzyme molecules. However, using OC-CALB preparations with maximum loading, CALB stability was greatly improved in different conditions after PEI coating. Moreover, the CALB release from the OC support in the presence of detergents, or during thermal or organic solvent inactivations was greatly reduced after this treatment (PEI plus DS coating). The results pointed that the main positive effect of this coating could be derived from the physical intermolecular crosslinking of the CALB molecules with the polymers that reduce the enzyme desorption from the support. The coating of OC-CALB-PEI with DS only produced a minimal improvement on enzyme performance. Even though the enzyme release was much more difficult after physical crosslinking, all enzyme molecules could be released from the OC support combining an ionic detergent (SDS), high buffer concentration, pH 3 and 45 °C, while using the OC-CALB just 2% SDS at pH 7 and 25 °C was enough to release all enzyme. The support could be reused several cycles. Thus, this strategy permitted to greatly reduce the enzyme desorption during operation and to improve enzyme stability while keeping the enzyme immobilization reversibility.